Sociodemographic, anthropometric and dietary determinants of dyslipidemia in preschoolers - Luciana N. Nobre; Joel A. Lamounier; Sylvia do C.C. Franceschini (Jornal de Pediatria (Versão em Português), 2013)
Objective: To investigate the determinants of dyslipidemia in preschoolers. Methods: A total of 227 preschoolers residing in an urban area of the city of Diamantina, Minas Gerais, Brazil were evaluated at age 5 years, using a cross-sectional design. Dietary intake from a food frequency questionnaire, anthropometric/biochemical parameters, and socioeconomic/behavioral information from a questionnaire were evaluated. ‘Mixed diet’, ‘snack’, and ‘unhealthy’ dietary patterns were identified using principal component analysis. The determinants of dyslipidemia were examined using Poisson regression analysis. Results: The prevalence of dyslipidemia in this study was 65.19%. Preschoolers who less frequently consumed foods in the ‘mixed diet’ dietary pattern had a higher risk of high concentrations of low-density lipoprotein cholesterol (PR = 2.30; p = 0.004) when compared with those with more frequent consumption of the ‘mixed diet’ dietary pattern. Preschoolers whose mothers had lower levels of education presented a lower risk of high concentrations of low-density lipoprotein cholesterol (PR = 0.43; p = 0.003), and preschoolers who were overweight/obese presented with greater risk of high concentrations of low-density lipoprotein cholesterol (PR = 2.23; p = 0.003). Conclusion: The determinants of dyslipidemia identified in this study were less frequent consumption of foods in the ‘mixed diet’ dietary pattern, higher body mass index, and higher level of maternal education. This study shows that despite the young age of the group under study, they already present a high prevalence of dyslipidemia, which is an important risk factor for cardiovascular disease.